Subcutaneous fat necrosis of the newborn: hypercalcaemia with hepatic and atrial myocardial calcification. Issue 4 (1st July 2003) - Dudink, J; Walther, F J; Beekman, R P
Abstract : Subcutaneous fat necrosis of the newborn (SCFN) is a very rare disorder, which can be complicated by hypercalcaemia and thrombocytopenia. The case is presented of an infant with SCFN and symptomatic hypercalcaemia, who developed calcifications in the liver, the inferior vena cava, and the atrial septum of the heart. The hypercalcaemia was treated with hyperhydration, frusemide, glucocorticoids, and a diet low in calcium and vitamin D. Clinical features, diagnosis, complications, and treatment of this rare condition are discussed.